2021
DOI: 10.3390/ijms22147514
|View full text |Cite
|
Sign up to set email alerts
|

A Novel NFIX-STAT6 Gene Fusion in Solitary Fibrous Tumor: A Case Report

Abstract: Solitary fibrous tumor is a rare subtype of soft-tissue sarcoma with a wide spectrum of histopathological features and clinical behaviors, ranging from mildly to highly aggressive tumors. The defining genetic driver alteration is the gene fusion NAB2–STAT6, resulting from a paracentric inversion within chromosome 12q, and involving several different exons in each gene. STAT6 (signal transducer and activator of transcription 6) nuclear immunostaining and/or the identification of NAB2–STAT6 gene fusion is requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The genetic hallmark of SFT is the recurrent gene fusion NAB2-STAT6, located in the chromosomal region 12q13, and involving several different exons in each gene. However, a novel gene fusion, NFIX-STAT6, was identified [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The genetic hallmark of SFT is the recurrent gene fusion NAB2-STAT6, located in the chromosomal region 12q13, and involving several different exons in each gene. However, a novel gene fusion, NFIX-STAT6, was identified [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that, although NAB2-STAT6 fusion accounts for almost all known SFT cases, recently we have reported one rare SFT case in which a different fusion type (NFIX-STAT6) was observed. 58 Nevertheless, our current ASO design strategy, which targets the 3′ UTR of STAT6, should also treat those SFT fusions.…”
Section: Discussionmentioning
confidence: 99%
“…Of the extrapleural SFTs, breast SFT remains the rarest, and histopathological and image diagnosis is both difficult and unsecured. In recent studies, NAB2-STAT6 or NFIX-STAT6 fusion gene was reported to be the driver mutation of SFT, which plays a key role in collagen production, vessel formation, and tumor proliferation [3,4,6] ; however, the IHC staining of preoperative STAT6 staining for breast SFTs are seldom reported, possibly due to its rarity. To our knowledge, 32 cases of breast SFT have been reported in previous case studies (Table S1, http://links.lww.com/MD/ I209).…”
Section: Discussionmentioning
confidence: 99%